An alternative approach to contralateral exploration in infants with unilateral inguinal hernia: Ultrasonography - Kazez, A.; Serhatlioglu, S.; Akfirat, M.; Cihangiroglu, M.; Saglam, M.; Demirbag, M. (My University, 1998)
This study was designed to determine the efficacy of preoperative ultrasonography (US) in the diagnosis of groin pathologies in infants. From August 1996 to March 1998, 60 infants under two years of age with clinically diagnosed inguinal hernia (IH) were referred for US scans for both sides of the groin. Bilateral operations were performed regardless of preoperative US evaluation results and comparisons were made between US diagnosis and intraoperative findings. US diagnosis of IH and patent processus vaginalis (PPV) proved to be 96 % accurate. US examination of 46 patients with clinically diagnosed unilateral IH; defined 13 IH and 12 PPV (a total of 25, in the opposite groin (54 %). In only one patient with normal opposite groin, US diagnosis proved to be wrong with an intraoperative PPV finding (5 %). The high productivity (97 %), sensitivity (92 %) and specificity (95 %) of US in identification of IH+PPV makes US a highly reliable diagnostic technique. In conclusion, US examination of the opposite groin should routinely be performed on patients with clinically diagnosed unilateral IH before surgical intervention.
Keywords: Children; Diagnosis; Inguinal hernia; Ultrasonography